AN ANALYSIS OF STUDENTâS READING SPEED OF DESCRIPTIVE TEXT AT VIII GRADE SMPN 1 RAMBAH SAMO - Kurniati, Nia; Rasyidah, Ummi; Kasyulita, Evi (Jurnal Ilmiah Mahasiswa FKIP Prodi Bahasa Inggris, 2015)
This research about reading speed students. The population of this research was 119 students. Thesamples in this research were 27 students. Researcher used cluster random sampling/random to takesamples that focus on one class. The instrument in this research is reading test. Based on a readingspeed skills test, the average speed of reading students, 2 students were able to reach 100-149 WPM inslow category and 25 other students are only able to achieve 50-99 WPM in very slow category. So,the skill of reading speed students at VIII grade in SMPN 1 Rambah Samo was very slow